CZY FAKTYCZNIE POD GRUNWALDEM ŚPIEWANO BOGURODZICĘ? - Obremski, Krzysztof (Prace Polonistyczne, 2021)
The answer to the question posed in the title of the article is negative. The two times that Bogurodzica was sung in July 1410 served as a verbal a praise of the Polish army’s piety and thus an important element of the propaganda war against the Teutonic Order; at the same time, these performances counterbalanced the futile siege of Malbork as well as the disproportion between the triumph on the battlefield and the outcomes of the Toruń peace treaty; on the international stage, they mitigated the allegations of the sinful alliance between Poles and the “Saracens” (Tatars) and the schismatics. Polish chroniclers treated the litany Kyrie eleison as pars pro toto: in their accounts, the two words of the chorus were transformed into a native song.